A exclusividade desinencial e a realização do sujeito 'eu' - De Moura Neves, Maria Helena [UNESP]; Goulart, Felipe Vivian (Universidade Estadual de Maringa, 2017)
The aim of this article is to explore the relationship between the expression of the subject pronoun eu and the presence of inflections which are exclusive to the 1st person singular. The speech of 13 vloggers native to different regions of Brazil served as corpus for this research, which is based on functionalist and sociolinguistic theories. The analysis revolves around the crossing of two factors: the possibilities offered by BP regarding 1st-person-singular subject representation (expression or ellipsis), and the possibilities related to verbal inflections, since the accompanying verb may (or may not) have an ending which unequivocally points to the 1st person singular. A clear preference for the overt subject having been discovered, we moved on to a discussion of the ways in which the presence of exclusive inflections interferes with this result. The results confirm the hypothesis that the absence of exclusive inflections produces a drastic rise in the expression rates of the subject pronoun; however, they do not confirm the hypothesis that the presence of such inflections leads to a significant decrease in said rates. This suggests the existence of other motivations behind the expression of eu besides the guarantee of a correct remission to the intended (exophoric) referent.
Inflectional exclusivity and subject 'eu' realization
Keywords: Ellipsis; First person; Inflections; Informality; Subject realization